The Effect of Project Based Learning (PjBL) on Physics Learning: A Meta-Analysis - Ukhlufi Khairi; Aprinaldi; Juwita Meri (Department of Physics Education, Universitas Mataram, 2023)
Ideally education should prepare students to be able to face challenges in the future. The physics learning process implemented by teachers in the classroom should be able to encourage the growth of 21st century skills in students. In reality, the learning process still uses conventional methods and teacher-centered, so that the ability of students is low. For this reason, PjBL is implemented to improve students’ abilities in physics subjects. The purpose of this study is to analyze the influence of similar research that use PjBL. The type of research used is meta-analysis research with a quantitative approach. The results of this research are the first, namely the impact of similar research from PjBL which indicates that PjBL has a positive impact on physics learning. Second, based on grade level, similar study effects of PjBL showed that grade X had a more significant effect. Thirdly, based on the learning materials, the impact of similar studies of PjBL shows that the topic of simple harmonic motion has a significant impact. Fourth, based on the learning media that has a more significant effect on similar research, namely LKS media. Fifth, based on the aspects reviewed, the impact of similar studies of PjBL indicated that the aspect of problem-solving ability has a more significant impact. This research can be used as a reference to develop PjBL at school levels, different materials, various interactive media, and aspects reviewed.